HUBUNGAN PARAMETER KUALITAS AIR TERHADAP DISTRIBUSI KELIMPAHAN FITOPLANKTON DI PERAIRAN TELUK MEULABOH ACEH BARAT - NENENG MARLIAN (Journal of Aceh Aquatic Sciences, 2017)
The reaserch on  relationship water quality parameters to the fitoplankton abundance distribution in Waters of Meulaboh Bay West Aceh  was  conducted  on  Mei-July 2014 in Meulaboh Bay. Sampling Location on each observation sampling points  as purposing sampling at 10 sites, wich consist of river, mouth river, bay waters, middle of bay to outer of bay. The purpose in this research  was to analysis relationship water quality parameters to the fitoplankton abundance distribution in  Waters of  Meulaboh Bay West Aceh. The result in this research showed that from the observation to the fitoplankton composition in waters were found 5 class of  fitoplankton such Cyanophyceace, Bacillariophyceae, Dinophyceaceae, Chrysophyceae, Clorophyceae, Euglenaphyceae and with the abundance fitoplankton values were sites A-E = 72.515-713.324.444 cell/m3 and sites F-J = 37.493-271.786.665 cell/m3. As well as fitoplankton abundance distribution deacreased toward the waters such  river and  mouth river but  fitoplankton abudance distribution increased toward the waters of edge bay was the coastal of bay. Relationship water quality parameters to the fitoplankton distribution showed that relationship wich negative correlation with the water quality parameters such transparancy, turbidity, dissolved oxcigen, nitrate, ortophosphate and silicate, but fitoplankton abundance had relationship wich positive correlation with the water quality parameters such themperature, current velodity, salinity and pH.